The genealogy of the early Kings of Aragón and Navarra. Un unpliblished document: letter of Pedro Jerónimo de Aponte with notes of Jerónimo Zurita (1565) - Extravís Hernández, Isabel (Huarte de San Juan. Geografía e Historia, 2017)
In 1562 is published the first part of the Annals of the Crown of Aragon of Jerónimo Zurita. In this work we can find the genealogy of the early Kings of Aragon and of them of Navarra. By means of a letter from Pedro Jerónimo Aponte sent to the aragonese chronicler we have find some discrepancies between the sources and the work style of both authors. The transcription of the letter from Aponte you and of them notes written Zurita, along with the text that on them exists in Anales allow us to follow both the succession of these early monarchs and what was written about them by several mediaval chroniclers.
Keywords: Jerónimo Zurita; Pedro Jerónimo de Aponte; Genealogy; Kings of Navarre; chronicle